2021
DOI: 10.1093/heapro/daab081
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a smartphone application-based intervention for encouraging children’s healthy eating in Denmark

Abstract: Summary The growing rates of childhood obesity constitute a public health challenge worldwide. Therefore it is important to identify effective and widely applicable interventions to prevent it. This study aims to explore children’s experience of using a newly developed smartphone application (app) designed to promote healthy eating and evaluate its efficacy on encouraging healthy eating. First, two focus groups were conducted to explore children’s experience of using the app. Then, a quasi-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Studies reported that parents' inclusion in programs elicited positive impacts on participants, irrespective of their level of involvement, and that positive behavior changes among participants diffused to their families and peers [46][47][48][49][50][51][52][53]. When considering parents' inclusion in programs, studies suggested that parental digital literacy needed to be considered as well as whether their involvement would detract from the independence adolescents would be attempting to achieve during this period of development [47,53,54].…”
Section: Role Of Families and Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that parents' inclusion in programs elicited positive impacts on participants, irrespective of their level of involvement, and that positive behavior changes among participants diffused to their families and peers [46][47][48][49][50][51][52][53]. When considering parents' inclusion in programs, studies suggested that parental digital literacy needed to be considered as well as whether their involvement would detract from the independence adolescents would be attempting to achieve during this period of development [47,53,54].…”
Section: Role Of Families and Communitiesmentioning
confidence: 99%
“…Studies reported that parents' inclusion in programs elicited positive impacts on participants, irrespective of their level of involvement, and that positive behavior changes among participants diffused to their families and peers [46][47][48][49][50][51][52][53]. When considering parents' inclusion in programs, studies suggested that parental digital literacy needed to be considered as well as whether their involvement would detract from the independence adolescents would be attempting to achieve during this period of development [47,53,54]. Conversely, the positive impact of including families in interventions needed to be balanced with intervention content that addressed interpersonal barriers to healthy eating, such as peer and family pressure, lack of parental support for healthy eating, lack of control over food at home and in social settings, and tensions with cultural foods and healthier food choices [52,55,56].…”
Section: Role Of Families and Communitiesmentioning
confidence: 99%
“…The use of high-quality mobile health (mHealth) applications (apps) represents one promising avenue for health promotion, with mHealth apps exploding in popularity over the past several years. Although more experimental research is needed, some evidence suggests that nutritionbased apps are helpful, especially for promoting fruit and vegetable consumption among children (12)(13)(14) . Sixty percent of parents in the US with children 12 years or younger reported that their children engage with smartphones, with 30% doing so before age five (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Many adolescents enrolled in outpatient obesity treatment programs, drop out prematurely, which greatly limits meaningful weight loss and long‐term outcomes 2,5 . In adults, digital apps for weight loss have been shown to be cost‐effective while improving access to care, optimizing adherence, and decreasing labour burden on clinical staff and clinicians 1,5‐9 . The efficacy of digital apps for weight management in youth is less clear 1,9,10 …”
Section: Introductionmentioning
confidence: 99%
“…2,5 In adults, digital apps for weight loss have been shown to be cost-effective while improving access to care, optimizing adherence, and decreasing labour burden on clinical staff and clinicians. 1,[5][6][7][8][9] The efficacy of digital apps for weight management in youth is less clear. 1,9,10 App-based intervention delivery may not only provide greater accessibility to evidence-based treatment, but it may also provide a vehicle to test novel behavioural intervention strategies.…”
mentioning
confidence: 99%